Kajian fonologi dialek Melayu Kabong / Salbia Hassan - Salbia , Hassan (2016)
The Kabong Malay dialect (DMKb) is one of the Sarawak Malay dialects. This study aims to identify the systems and structures of the phonology of DMKb. To achieve these objectives, the data was collected using the upstream field research method (Asmah Haji Omar, 2008b), as there has been no such study on this dialect previous to this. The analysis was done according to the theory of descriptive linguistics (Bloomfield 1933, Robins 1968, Asmah 2006, 2008a, 2012). Eight vowel phonemes have been identified in DMKb; four front vowel /i/, /e/, //, /a/; one central vowel //; and three back vowels /u/, /o/ and //. There are 19 consonant phonemes in the inventory, namely, seven plosives /p/, /b/, /t/, /d/, /k/, //, //; three fricatives /s/, //, /h/; two affricates /t/, /d/; four nasals /m/, /n/, / / and //; one lateral /l/ and two semi-vowels /w/ and /j/. Only fronting vowels clusters found in DMKb and the consonant clusters which fall into two patterns; Nasal-Oral (NOr), and Oral - Oral (OrOr). Syllables are of the structures V, VK, KV, KVV, KVK, KKV and KKVK. They form the bases of the phonology of words which is reflected in monosyllables, disyllables, trisyllables, but the majority are disyllables. Words with more than three syllables appear to be loans from English through standard Malay.